Convolution on spaces of locally summable functions - Federica Andreano; Renato Grande (Journal of Function Spaces and Applications)
In this work we prove the existence of convolution on Marcinkiewicz spaces 𝔐p(ℝ), 1≤p<∞, and, using pointwise approximate identities, we extend the classical definition of Hilbert transform to such spaces.